Effect of Ulinastatin on Early Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Surgery: A Systemic Review and Meta-Analysis - Duan, Mei; Liu, Fangyan; Fu, Huiqun; Feng, Shuai; Wang, Xue; Wang, Tianlong (Frontiers in Neuroscience, 2021)
Abstract Background: Postoperative cognitive dysfunction (POCD) is associated with neuroinflammation by triggering the systemic inflammatory responses. Related studies have demonstrated that ulinastatin, which is a urinary trypsin inhibitor, inhibited the release of inflammatory mediators and improved postoperative cognitive function in elderly patients undergoing major surgery. However, there are controversial results put forwarded by some studies. This systemic review aimed to evaluate the effect of ulinastatin on POCD in patients undergoing surgery. Methods: We searched PubMed, EMBASE, Cochrane Library, Web of science and Ovid to find relevant randomized controlled trials (RCTs) of ulinastatin on POCD in patients undergoing surgery. The primary outcomes included the incidence of POCD and the MMSE scores. The secondary outcome was the levels of inflammatory cytokines such as TNF-α, S100β, CRP, IL-6 and IL-10. RevMan 5.3 was used to conduct the meta-analysis. Results: Ten RCTs were included finally. Compared with controls, ulinastatin significantly reduced the incidence of POCD (RR=0.29, 95%CI 0.21-0.41, test of RR=1 : Z=7.05, P<0.00001). In addition, patients in ulinastatin group have lower levels of TNF-α, S100β, CRP and IL-6 and higher level of IL-10 in serum following surgery. Conclusion: These findings suggested that ulinastatin can be used as anti-inflammatory drug for POCD prevention in elderly patients undergoing surgery.